Doing our work in a good way: A framework of collaboration and a case for Indigenous-only writing classrooms - Toorenburgh, Lydia; Gaudet, Loren (Discourse and Writing/Rédactologie, 2024)
Since fall of 2021, UVic has offered a section of the foundational writing course, ATWP 135: Intro to Academic Writing that is dedicated for Indigenous students. This course provides a space for first-year Indigenous students to find a sense of belonging with each other and in the university more broadly, experience anti-oppressive grading practices (Gaudet 2022), develop the confidence to access Indigenous student supports, and navigate the broader institution. In this article, the authors (an Indigenous staff working as the Tri-Faculty Indigenous Resurgence Coordinator and a non-Indigenous faculty serving as the course instructor) discuss the development, delivery, and impact of this initiative. We share an example of promising practice for institutions to consider in the interest of supporting Indigenous student success and retention. In doing so, we also offer a model for collaboration across disciplines and across cultures based on shared values of vulnerability, openness, and honesty.